"Can you see me?" Videoconferencing and eating disorder risk during COVID‐19: Anxiety, impairment, and mediators. Issue 1 (4th November 2022) - Hart, Laura M.; Mitchison, Deborah; Fuller‐Tyszkiewicz, Matthew; Giles, Sarah; Fardouly, Jasmine; Jarman, Hannah K.; Damiano, Stephanie R.; McLean, Siân A.; Prichard, Ivanka; Yager, Zali; Krug, Isabel
Abstract: Objective: The use of videoconferencing has increased during the pandemic, creating prolonged exposure to self‐image. This research aimed to investigate whether eating disorder (ED) risk was associated with videoconferencing performance for work or study and to explore whether the use of safety behaviors and self‐focused attention mediated the relationship between ED risk and perceived control over performance anxiety, impaired engagement, or avoidance of videoconferencing for work or study. Method: In 2020, an online survey was distributed within Australia to those aged over 18 years via academic and social networks, measuring: use of videoconferencing for work/study, demographics, ED risk, safety behaviors for appearance concerns, self‐focused attention, perceived control over performance anxiety, perceived engagement impairment, and avoidance of videoconferencing. A total of 640 participants (77.3% female, M age  = 26.2 years) returned complete data and were included in analyses. Results: 245 participants (38.7%) were considered at‐risk for EDs (SCOFF > 2). Those at‐risk reported significantly more safety behaviors, self‐focused attention, impaired engagement, and avoidance, plus lower perceived control over performance anxiety than those not at‐risk. Multiple mediation models found the effects of ED risk on control over performance anxiety, impaired engagement, and avoidance were partially mediated by safety behaviors and self‐focused attention. Discussion: Our cross‐sectional findings suggest videoconferencing for work/study‐related purposes is associated with performance anxiety, impaired engagement, and avoidance among individuals at‐risk for EDs. Poorer videoconferencing outcomes appear more strongly related to social anxiety variables than ED status. Clinicians and educators may need to provide extra support for those using videoconferencing. Public Significance: Because videoconferencing often involves seeing your own image (via self‐view) we wondered whether the appearance concerns experienced by those with eating disorders (EDs) might interfere with the ability to focus on or to contribute to work/study videoconferencing meetings. We found that although those with EDs experience more impairments in their videoconferencing engagement/contribution, these were linked just as strongly to social anxiety as they were to appearance concerns.